Teores pseudo totais de bário em solos com características contrastantes - Rizzardo, Joseane (2020)
The pedological development has not been considered to establish the quality reference values (QRV) of trace elements, although the content of such elements is a result of soil-forming factors and processes. The aim of this study was to verify if soil barium (Ba) content is associated with soil attributes that express pedological development. Fifty-six areas without known human influence (native grasslands) and from igneous and sedimentary (sandstone) rocks were sampled (0-0.2 m). Soil chemical and physical attributes (clay, sand and silt), and the semitotal content (USEPA 3051A method) of Ba and other trace elements were determined. Pearson's correlation and a principal components analysis were used to verify the association of Ba with the evaluated variables and the variability of the samples. In addition, clustering of soil samples (dissimilarity classes) was studied. The contents of Ba correlated strongly (r = 0.70 to 0.90), with the semitotal contents of Zn and Co, besides Mnd (extracted with sodium dithionitecitrate- bicarbonate). Moderately correlation (r = 0.50 to 0.70) was found for the acidity indicators (base saturation, Al3+, Mg2+, Ca2+, K+, sum of the last three cations and pHH₂O) and silt and semitotal Cu contents. About 65% of the accumulated variance was related with the analyzed variables, and Ba variability was more important in Component 1 of the multivariate analysis. The highest variances were found for this metal and some attributes (pHH₂O, Al3+, V, Fed, Mnd, Co, Cu, Ni, V and Zn). Average contents of Ba were lowest in Group 1 soils (39.61 mg/kg), while highest contents were found in Group 4 (464.26 mg/kg). Intermediate average Ba contents were found in Group 2 and 3 soils (120.04 and 225.44 mg/kg, respectively). Barium contents vary with chemical characteristics and texture, expressing the pedological development. Less developed soils, clustered in Group 3 and 4, with higher contents of Ca2+, Mg2+, K+ and silt, and lower contents of Al3+, have higher contents of Ba. The content of this metal in these groups are higher than the Brazilian legislation guidelines. Our results indicate the importance of considering pedological development to update these values. Key words: 1. Natural soil. 2. Natural contents. 3. Environmental monitoring. 4. Guiding values. 5. Trace elements.